1982
DOI: 10.1007/bf01825036
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical facies model of ore formation in the Grythyttan-Hällefors area, Bergslagen, Central Sweden

Abstract: With 8 figures ZusammenfassungDie verschiedenen Eisen-und Manganerz-Bildungen des Grythyttan-H~illcfors-Gebietes zeigen Verhaltnisse auf, die einem systematischen Wechsel der Bedoxbedingungen wiedergeben, yon oxidischer B~indereisenerzbildung bis hin zu stark reduzierten graphitfiihrenden Schiefem. Dieses Phanomen wird durch ein Fazies-Modell erkl~rt. Die unterschiedliehen Mflieu-Bedingungen werden auch als Ursache ffir die geochemische Diferentiation unedler Metall-Ablagerungen in Cu-Erze angesehen, die mit M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Conclusions. Previous work (Zakrzewski, 1982;Oen et al, 1982) has suggested that the Ag-bearing H~illefors deposits were probably formed by the action of metamorphic solutions on sediments of volcano-sedimentary origin. Carbonates, especially the black carbonates, appear to have acted as collectors of the metal compounds.…”
Section: T~ Copyright the Mineralogical Societymentioning
confidence: 99%
“…Conclusions. Previous work (Zakrzewski, 1982;Oen et al, 1982) has suggested that the Ag-bearing H~illefors deposits were probably formed by the action of metamorphic solutions on sediments of volcano-sedimentary origin. Carbonates, especially the black carbonates, appear to have acted as collectors of the metal compounds.…”
Section: T~ Copyright the Mineralogical Societymentioning
confidence: 99%
“…Recently, both of these ore types have been interpreted as volcanic-exhalative formations (FRIETSCH, 1982;ZAKRZEWSKI, 1982). However, MAGNUSSON (1970) The geological field observations in the Ammeberg ore zone have been documented in detail by HENRIQUES (1964) andHEDSTROM et al (1989).…”
Section: Introductionmentioning
confidence: 94%
“…The Bergslagen metallogenic province has more than 2000 iron and more than 200 base metal (predominantly of the Ag Pb-Zn + Cu type) deposits and is a producer of Mn, Co, W, Mo, Au, Bi, Ce, Hg, and Se. The H/illefors silver deposit could be considered as an original volcanogenic-exhalative iron ore deposit, in the sense proposed by Large (1977) and by Zakrzewski (1982). It is presumed to have contained dispersed amounts of Ag-Pb-Zn-(+ Cu); subsequently, secondary mobilization of metals occurred due to an increase in temperature and to a lesser extent pressure, followed by the precipitation of sulphides and sulphosalts with decreasing temperature and changes of sulphur and oxygen activities.…”
Section: (~ Copyright the Mineralogical Societymentioning
confidence: 99%
“…These considerations confirm the author's conclusions in previous studies (Jasiflski, 1983) Conclusions. Zakrzewski (1982) proposed a geochemical facies model to account for the distribution of different ore types at H/illefors relative to their position in the stratigraphy with oxidesilicate-carbonate and sulphide facies corresponding to levels in a Na-leptite-K-leptite-sediment sequence. He also proposed that all the ores had a common mafic volcanogenic origin.…”
Section: (~ Copyright the Mineralogical Societymentioning
confidence: 99%